Effects of Wx Genotype, Nitrogen Fertilization, and Temperature on Rice Grain Quality - Xia, Duo; Wang, Yipei; Shi, Qingyun; Wu, Bian; Yu, Xiaoman; Zhang, Changquan; Li, Yanhua; Fu, Pei; Li, Minqi; Zhang, Qinglu; Liu, Qiaoquan; Gao, Guanjun; et al. (Frontiers in Plant Science, 2022)
Rice quality is a complexed trait, which is not only the key determinant of rice market value, but also one of the most important restrictive factors in rice breeding. It is influenced by both genetic and environmental factors. However, the combined effects of genotypes and environmental factors on rice grain quality remain unclear. In this study, we performed three-factor experimental design to explore the response of rice grain quality to different Wx genotypes, nitrogen fertilization and temperature during grain filling stage. We found that the three factors contributed differently to rice taste, appearance and nutritional quality. The increase of Wx function and nitrogen fertilization level significantly reduced rice eating quality, whereas high temperature almost had no effect on rice eating quality. The main effect of temperature on appearance quality and moderate Wx function at low temperature contributed to better rice appearance, while higher nitrogen fertilization level promoted appearance at high temperature. For nutritional quality, Wx gene promoted amylose content as well as starch-lipids content, nitrogen fertilization elevated storage protein content while higher temperature increased lipids content but decreased protein content. This study helps to broaden the public understanding of the major factors that affect rice quality and provides constructive messages for rice quality improvement and the cultivation of high-quality rice varieties.